An introduction to sociocultural anthropology : adaptations, structures, meanings - ZERIHUN DODA (ETHIOPIA: HALL, 2005)
"A concise yet comprehensive guide to cultural anthropology using a materialist approach. This revised and updated edition exposes students to the cultural detail and personal experiences that lie in the anthropological record and extends their anthropological understanding to contemporary issues"--Provided by publisher.
"The first edition of this book was previously published by: Pearson Education, Inc."--Title page.
Includes bibliographical references and index.
Keywords: Ethnology; Human geography; Ethnobiology